2017
DOI: 10.15406/ghoa.2017.06.00187
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield for Endoscopy in Patients with Altered Bowel Habits

Abstract: Background: Alterations in bowel habits is one of leading complaints among patients seen in the gastroenterology office. The increased volume of patient with complaints of chronic diarrhea, constipation or altered bowel habits continues to raise the question of the appropriateness and role for endoscopy as part of the diagnostic workup regarding these increasingly prevalent complaints. There is currently no clear evidence as to when endoscopy should be performed in evaluation of altered bowel habits. Many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…On the other hand, for patients with digestive complaints, endoscopic evaluations have set the gold standard. Wood et al analyzed 300 consecutive patients with digestive complaints and concluded that an endoscopy was unlikely to uncover a diagnosis to explain altered bowel habits or dyspepsia [16]. However, they recommended an initial non-invasive workup, such as a CT scan, as a reasonable option to identify a likely diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for patients with digestive complaints, endoscopic evaluations have set the gold standard. Wood et al analyzed 300 consecutive patients with digestive complaints and concluded that an endoscopy was unlikely to uncover a diagnosis to explain altered bowel habits or dyspepsia [16]. However, they recommended an initial non-invasive workup, such as a CT scan, as a reasonable option to identify a likely diagnosis.…”
Section: Discussionmentioning
confidence: 99%